Determination of the Origin of Children Strengthens Legal Protection of the Status of Children due to the Rejection of Itsbat Nikah - Paradika Rhassely Adi Pratama; Dinda Nailatus Syaadah; Anis Nuru Aini; Irma Maulida; Gusti Yosi Andri (International Journal Labs, 2025)
The rejection of the marriage itsbat application directly impacts the legal status of the child born, as the parents' marriage is not legally, religiously, or customarily recognized. This study aims to analyze the legal consequences of the rejection on the child's position and examine the determination of the child's origin as a form of legal protection. Using a normative juridical approach, this study analyzes legal materials related to the status of children born from sirri marriages. The results of the study show that children born from sirri marriages only have a legal relationship with their mother. Moreover, if the itsbat application is rejected, the child will not be recognized as the legitimate child of their biological father. This has consequences on the child's access to administrative, inheritance, and guardianship rights. Remarriage also does not alter the child's position because, according to Islamic law, the sirri marriage is invalid and thus rejected by itsbat. As a result, the child remains an out-of-wedlock child. The determination of origin by the court is an alternative protection that allows the inclusion of the biological father's name in the population document and provides limited space for the child's civil rights. These limitations are also reaffirmed in the Fatwa of the Indonesian Ulema Council, which states that the biological father's obligation is limited to providing living support and a mandatory will. The conclusion of this study emphasizes the importance of determining origin as an instrument for the legal protection of children in the national legal system, especially regarding the rejection of the marriage itsbat application.